Convection in rotating non-uniformly stratiﬁed spherical ﬂuid shells: a systematic parameter study - ŠIMKANIN, Ján; HEJDA, Pavel; JANKOVIČOVÁ, Dana (Contributions to Geophysics and Geodesy, 2009)
A systematic parameter study of rotating convection in non-uniformly stratiﬁed spherical shells in dependence on the Prandtl number, Ekman number and  Rayleigh number is presented.  Attention is focused  on  the  case,  in  which  the thickness of both sublayers (stable and  unstable)  is the same  (which  was not investigated before).   In our case the  convection is not suppressed in the stably stratiﬁed region but,  it is developed  in both  sublayers.  Cases  of small  and  large  Prandtl numbers are  characterized  by the  creation  of multilayer  convective  structures.  Convective motions  take place  simultaneously in the  stable  and  unstable layers  and  form a multilayer structure.  On the other hand,  it is not possible  to observe  any multilayer convection for Prandtl number equal  to one but it is possible to observe  the small-scale  structures.  A conclusion  is that our case is similar to the  case in which the  thickness of unstable sublayer is greater than that of stable  one.